Critical control points at the level of collection, processing and preservation of Sahiwal bull semen - PANKAJ, P K; RAINA, V S; ROY, B; MOHANTY, T K; GUPTA, A K (The Indian Journal of Animal Sciences, 2011)
The present investigation was conducted on Sahiwal bulls to study the various critical control points in frozen semen processing. On each collection, 2 ejaculates were taken in succession and examined for various standard laboratory tests (mass activity, individual motility, non-eosinophilic count, sperm abnormalities, acrosomal integrity, microbial load etc.). The various critical control points under study were sterilization method for glassware or collection tube of artificial vagina, treatment of water to be used for making extender, sterilization method for buffer to be used for making extender, processing room temperature and osmolality of extender. Microwave oven method of sterilization was superior to hot air oven taking into account the time saving. The Resin based water purification system was better than triple distilled water and water obtained from this system should not be stored for more than 3 days. Both methods of buffer treatment (autoclaving/filtration) were equally effective in terms of semen quality and microbial count. Osmolality of extender should be kept between 240 to 260 mOsmol/kg to maintain optimum quality semen. Processing room temperature should be kept in the range of 22 to 24°C for quality semen production. The results indicated that critical control points monitoring should be made mandatory for all semen processing laboratories. Further in vivo study with various treatments should be carried out to test its real field applicability.